ALX4 related parietal foramina mimicking encephalocele in prenatal period†. (17th May 2016) - Saraç Sivrikoz, Tugba; Altunoglu, Umut; Kalelioglu, İbrahim Halil; Yüksel, Atıl; Uyguner, Oya Zehra; Has, Recep; Kayserili, Hülya
Abstract : What's Already Known About This Topic? PFM is an autosomal dominantly inherited genetic condition, caused by mutations in ALX4 and MSX2 genes. Reports on prenatally diagnosed cases are rare, and encephalocele remains the most leading differential diagnosis. What Does This Study Add? The full clinical spectrum of autosomal dominant ALX4‐related PFM in affected family members can be demonstrated through identification of a prenatal case, by close collaboration of perinatologists and clinical geneticists, as in the four generation family reported herein.